Factors Influencing the Intention to Use Computer Technology For E-Learning Among University Students - Jaafar, Juliana Rosmidah; Poongavanam, Nalinah; Lee, Su Yee; Ramalu, Jaya Chitra (UUM Press, 2023)
The utilisation of gadgets and computer technology has become a significant aspect of e-learning. This condition requires students to use various online platforms for learning purposes. The current study aims to explore the potential factor in explaining the intention to use computer technology during e-learning among private university students. Online questionnaires were distributed to 174 university students from various programmes in a university in Selangor. The items in the questionnaire covered three independent variables: perceived ease of use of technology, perceived usefulness of technology, and computer self-efficacy. The dependent variable is the intention to use computer technology in e-learning. Pearson Correlation was used to assess the relationship between the independent and dependent variables. Furthermore, Hierarchal Multiple Regression analysis was used to determine the predictor of the intention to use computer technology. The result showed that the intention to use computer technology for e-learning was significantly related to technology’s perceived ease of use, usefulness, and computer self-efficacy. However, when computer self-efficacy is controlled, students’ intention to use computer technology is driven by their perceived notion that technology is easy to use and usefulness of the technology. The study concludes that when students perceive technology as easy to use and sense its practicality, they will have a stronger intention of using technology for learning. This research implies that a systematic strategy should be practised by integrating computer technology into teaching and learning in the current situation. Future studies could further explore the potential of differences across students’ backgrounds towards e-learning.